The Role of Social Entrepreneurs in Fostering Creative Economy: A Comprehensive Bibliometric Analysis - Nanny Mayasari; Ade Suhara; Edy Santoso; Poetri AL-Viany Maqfirah; Hilda Yuliastuti (West Science Social and Humanities Studies, 2024)
This study provides a comprehensive bibliometric and co-authorship analysis of the field of social entrepreneurship and the creative economy. By examining thematic clusters, research trends, emerging opportunities, and author collaborations, the analysis reveals key insights into the evolution and current state of this interdisciplinary domain. Thematic clusters highlight the integration of social entrepreneurship, social innovation, and creative industries, emphasizing their interconnectedness. Research trends indicate a shift from foundational concepts to the inclusion of entrepreneurial ecosystems, sustainability, and the impact of technology and support structures. Identified research opportunities suggest further exploration of synergies between social and creative entrepreneurship, enhancement of support systems, and assessment of long-term impacts. Co-authorship analysis underscores the collaborative nature of this field, while also identifying areas for increased interdisciplinary integration. These findings offer valuable guidance for researchers, educators, policymakers, and practitioners aiming to advance knowledge and practice in social entrepreneurship and the creative economy.